Karsinoma Nasofaring: Faktor Risiko, Deteksi Dini, Diagnosis, dan Tata Laksana: Hasil Penelitian - Evita Zevanya; Iswarini, Arin Dwi (PT Kalbe Farma Tbk., 2025)
Nasopharyngeal carcinoma is a malignant tumor originating from nasopharyngeal epithelium; it is endemic in several regions, including Indonesia. This malignancy is the fourth most frequent cancer case in Indonesia. The etiology is not fully understood. The risk factors involve interactions between genetic and environmental factors, including age, gender, family history of nasopharyngeal carcinoma, consumption of fermented foods, and Epstein-Barr virus (EBV) infection. Early detection used EBV serology, EBV DNA plasma, and endoscopy; the IgG NPC strip is commonly used in Indonesia. The gold standard for diagnosis is biopsy and histopathological examination. The management of the disease depends on its stage. Intensity-modulated radiotherapy (IMRT) has shown several advantages over conventional radiotherapy. Follow-up is necessary to evaluate the outcome and remission.